Regulation of simian virus 40 early transcription in vitro by a purified tumor antigen. - Rio, D (1980)
Cloned DNA templates were used to direct the transcription of early and late simian virus 40 (SV40) genes by a cell-free RNA-synthesizing system. Transcription by RNA polymerase II was sensitive to low levels of alpha-amanitin and completely dependent on exogenously added DNA template. RNA products of discrete lengths were efficiently synthesized when transcription was directed by DNA restriction fragments containing promoter sequences for either early or late genes of SV40. Addition of the D2 tumor antigen to the template DNA inhibited transcription originating from the SV40 early promoter. In contrast, the D2 protein had little or no effect on the transcription from SV40 or adenovirus 2 (Ad2) late promoter sequences. When a mixture of cloned DNA containing SV40 early promoter and Ad2 late promoter was used to direct RNA synthesis, the D2 protein specifically inhibited the synthesis of SV40 early genes but not that of Ad2 late sequences. The D2 DNA binding protein also had no effect on the transcription directed by SV40 mutant templates that contain an intact early promoter sequence but lack specific tumor-antigen binding sites. We have confirmed that, under the conditions of the transcription assay, the D2 protein binds and interacts specifically with its recognition sites on wild-type template DNAs but fails to bind to mutant or Ad2 DNA templates that lack sequences containing SV40 tumor-antigen binding sites. These findings provide evidence that a direct interaction between tumor antigen and its specific binding sites on DNA is the mechanism by which the SV40 A gene autoregulates its transcription.